Reconstruction of Little Ice Age Events in the Canadian Rocky Mountains - Luckman, B. (Géographie physique et Quaternaire, 1986)
ABSTRACTThe well-developed moraines of the Little Ice Age represent the most significant regional Holocene glacial event in the Canadian Rocky Mountains. The application of dating techniques (documentary sources, dendrochronology, lichenometry and radiocarbon dating) appropriate to this timeframe are briefly reviewed and summary data from 33 glaciers are presented. Three main periods of moraine development are recognised (i) 1500-1700 A.D., represented by small fragments of poorly dated moraines, (ii) early 1700's when about one-third of the glaciers show a maximum advance, (iii) mid-to-late-nineteenth century when major readvances built moraines close to or beyond (i) and (ii). In addition to these periods, 14C dates from overridden trees indicate a 12th/13th century glacial advance to within 400 and 1400 m of the Little Ice Age Maximum positions at Robson and Kiwa (Premier Range) Glaciers respectively. Prior to this advance a period of warmer conditions is inferred between ca. 700-1100 A.D. from the presence of large, 14C-dated snags at tree-line near the Athabasca Glacier, including a 1000 14C yr-old larch (probably Larix lyallii) about 90 km northwest of its present limit. Tree-line may have readvanced at the Athabasca site between ca. 1300-1700 A.D. but receded again during the eighteenth and nineteenth centuries. Future research should be directed towards using the relatively long tree-ring records (500-1000 yrs, with cross-dating) of this area for climatic reconstructions.